Utilization of surplus tomatoes (Solanum lycopericum) as an alternative food colorant to pork tocino. - Intoy, Alyssa Camille B.
Tocino in the Philippines is a popular processed meat product with added preservatives, sugar, and artificial food coloring. Since there is a growing demand for sustainable and natural food components, this study was aimed at the utilization of lycopene extract from surplus tomatoes as an alternative food colorant to pork tocino. This is due to the fact that lycopene is a carotenoid that provides fruits a natural red color, thus, it is considered as an alternative food colorant. Tomatoes were dehydrated at 70°C for 16 hour. It was followed by the extraction methods by Kehili et al., (2019), and utilized virgin coconut oil as solvent. The extracted lycopene was added during the production of pork tocino. Results of the study showed the average lycopene content of about 9.8904 μg/g. Then, following a first order kinetics model, lycopene degradation was discovered to be influenced by oxidation, light exposure, and temperature fluctuations. Moreover, color degradation analysis showed a gradual loss of pigmentation, with L x b values correlating most with color changes in the pork tocino. Subsequent preference ranking tests then revealed that Formulation 1 containing 20% lycopene content was the most preferred. Lastly, in the general acceptance test, it was found out that aroma and color of the MPF and the commercial tocino was similar, both having "like very much" and "like moderately" for the utilization of surplus tomatoes not only as a natural food colorant, but also in producing food products that have sustainable and healthier components.